Tempe Juice As An Alternative Treatment For Anemia In Adolescent Girls - Yulianingsih, Endah; Porouw, Hasnawatty Surya; Podungge, Yusni; Igirisa, Yusni; Yanti, Febri Dwi (Universitas Aisyah Pringsewu, 2021)
The highest prevalence of anemia is found in Southeast Asia, with an estimated 60% of children experiencing anemia. Young women are at a higher risk of developing anemia compared to boys. Anemia has a negative impact on adolescents which can cause physical growth, behavioral and emotional disorders. This study aims for this study to see the effect of tempeh spice juice on increasing hemoglobin levels in adolescent girls. The research design was quantitative pre-experiment using the One Group Pre Test-Post Test design. The research subjects were 30 young women who were included in the inclusion criteria. This study was tested using the statistical paired sample t-test, obtained sig 0.002 less than 0.005. The average hemoglobin level before being given tempeh spice juice was 13, 123 and the average hemoglobin level after being given tempeh spice juice was 13, 910. The results of this study have a significant effect on the presentation of tempeh spice juice on the hemoglobin levels of adolescent girls. The results of this study can be used as an alternative in an effort to reduce the prevalence of anemia, with naturally occurring preparations that make it more plausible for young women.